Gender-Based Variations in Crime: Case Studies and Data Analy (Medico Legal Update, 2025)
This study examines gender differences in crime, a long-standing area of interest within sociology, criminology, psychology, and law. Consistent global patterns reveal that men commit more crimes, particularly violent offenses, than women, though gender also shapes victimization experiences and justice system responses. By analysing statistical trends, types of crimes associated with each gender, and the underlying social, cultural, and biological factors, this research highlights the complex interplay influencing criminal behaviour.In addition to addressing problems of traditional criminological theories, this research critically reviews important theoretical frameworks that explain gender variations in criminal behaviour. It investigates how gender norms or gender stereotypes, cultural expectations, and institutional practices shape outcomes within the justice system. Learning more about these elements is crucial for crafting effective crime prevention strategies, implementing gender-sensitive policies, and ensuring fair treatment across the criminal justice process. Ultimately, the study adds to broader conversations about social justice, gender equity, and the creation of more inclusive and just societies. The findings underscore the persistent gender gap in criminal behavior, shaped by complex social, cultural, and structural factors, and highlight the need for gender-responsive policies to promote fairness and equity within the justice system.